1. EVALUATION OF THE SAFETY AND FEASIBILITY OF USING A 7F INTRODUCER SHEATH VIA THE RADIAL ARTERY APPROACH (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the safety and feasibility of using 7F Introducer Sheath via the radial artery in complex coronary interventions.Methods: A prospective cross-sectional study was conducted on 63 patients undergoing percutaneous coronary intervention via the radial artery with 7F Sheath at the Vietnam National Heart Institute, Bach Mai Hospital, from October 2023 to June 2025.Results: The success rate of 7F Sheath placement was 100%. Complications at the puncture site included radial artery spasm (11.1%), hematoma (9.5%), with no cases of acute radial artery occlusion, perforation, or arteriovenous fistula. The mean radial artery diameter was 2.6 ± 0.2 mm, positively correlated with height (r = 0.67, p < 0.001) and weight (r = 0.58, p < 0.001). Females had a higher spasm rate than males (57.1% vs. 5.4%, p = 0.002).Conclusion: The use of 7F Introducer Sheath via the radial artery is safe and feasible, with a high success rate and low vascular complications.
Keywords: Percutaneous coronary intervention; radial artery; 7F Introducer Sheath